2005
DOI: 10.1021/ja043501j
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Intein that Can Be Inhibited with a Small Molecule Ligand

Abstract: Protein splicing is a process in which an intervening sequence, the intein, catalyzes its own excision out of a larger polypeptide precursor by joining the flanking sequences, the exteins, with a native peptide bond. Inteins are almost completely promiscuous toward the nature of their extein sequences and can be inserted into virtually any host protein. The intein-mediated formation of a peptide bond between two polypeptides offers great potential to modulate protein structure and, hence, protein function on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Other more recently emerging exciting avenues for protein engineering approaches rely on protein trans-splicing. This reaction is performed by split inteins, which are found in a few native examples (10,11) or can be created artificially from a regular intein (12)(13)(14)(15)(16)(17)(18)(19). Protein trans-splicing enables the post-translational linkage of proteins or polypeptides originating from two separate molecules.…”
mentioning
confidence: 99%
“…Other more recently emerging exciting avenues for protein engineering approaches rely on protein trans-splicing. This reaction is performed by split inteins, which are found in a few native examples (10,11) or can be created artificially from a regular intein (12)(13)(14)(15)(16)(17)(18)(19). Protein trans-splicing enables the post-translational linkage of proteins or polypeptides originating from two separate molecules.…”
mentioning
confidence: 99%
“…This has found in vivo applications such as the controllable generation of firefly luciferase in cultured cells and in Drosophila melanogaster [58], and PTS of a tobacco etch virus protease in yeast [59]. A mutated form of FKBP12 can be used to induce spontaneous reassociation and PTS of the split intein; in this case, the addition of rapamycin prevents reassocation and inhibits splicing [60]. Recently, Silver and coworkers demonstrated that the FKBP12 and FRB domains could be replaced with complementary coiled coil domains to induce luciferase activity in mammalian cells via specific coiled coil interactions rather than addition of a small molecule, presumably by inducing PTS of the luciferase segments [61].…”
Section: Reviewmentioning
confidence: 99%
“…While such modules have been developed with intact inteins, [38] split inteins provide an optimal platform for CPS, given that control over fragment complementation inherently implies control over protein splicing. Indeed split intein CPS systems have been engineered to be responsive to small molecules, [39, 40] light, [41-43] and proteolysis. [41] In an interesting recent study from Mootz and coworkers, an artificially split SspDnaB intein was outfitted with an uncleavable isopeptide bond bearing a peptidyl side-chain at position 1 of the N-intein and a photo-cleavable 4,5-dimethoxy-2- nitrobenzyl (DMNB) group capping the N-terminus in place of an N-extein.…”
Section: History and Applications Of Protein Trans-splicingmentioning
confidence: 99%